2012
DOI: 10.1016/j.jccase.2012.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Aortic prosthetic graft infection accompanied with esophagomediastinal fistulas: A case report

Abstract: Prosthetic graft infection is difficult to diagnose early, and hence, is associated with high mortality and morbidity rates. A 63-year-old man who had undergone surgical prosthetic replacement for an inflammatory thoracic aortic aneurysm 10 months previously visited our emergency room, complaining of chills, shivering, frequent vomiting, and back pain. He was diagnosed with severe sepsis, and a blood culture detected Streptococcus anginosus and Prevotella oralis. Repeated contrast-enhanced computed tomography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
3
1
Order By: Relevance
“…Repetitive mechanical damage due to arterial pulsation, esophageal wall circulation interruption by an enlarged aneurysm, and persistent vascular prosthesis infection are believed to cause AEF ( 6 ). A previous report described a case diagnosed with aortic prosthetic graft infection accompanied by aorto-enteric fistula after vascular surgery ( 7 ); however, in the present case, the thoracic aortic aneurysm had gradually increased in size because of a perigraft endoleak after aortic reconstruction without any sign of infection. Of note, it is extremely interesting that the patient's conditions started to worsen and he developed sepsis after the upper endoscope examination.…”
Section: Discussioncontrasting
confidence: 52%
“…Repetitive mechanical damage due to arterial pulsation, esophageal wall circulation interruption by an enlarged aneurysm, and persistent vascular prosthesis infection are believed to cause AEF ( 6 ). A previous report described a case diagnosed with aortic prosthetic graft infection accompanied by aorto-enteric fistula after vascular surgery ( 7 ); however, in the present case, the thoracic aortic aneurysm had gradually increased in size because of a perigraft endoleak after aortic reconstruction without any sign of infection. Of note, it is extremely interesting that the patient's conditions started to worsen and he developed sepsis after the upper endoscope examination.…”
Section: Discussioncontrasting
confidence: 52%
“…Some papers suggested that combined surgery provided better outcomes for some patients of secondary AEF [ [7] , [8] , [9] ] ( Table 2 ). What they suggested in common is that the first treatment of secondary AEF is infection control, with esophagectomy being the first stage.…”
Section: Discussionmentioning
confidence: 99%
“… Year Author [Reference] Number of cases Surgery of fistula Outocomes 2012 A. Saito et al [ 4 ] Six cases (four after TEVAR and two after open graft replacement) Five cases received staged surgery and one received simultaneous it. Two in-hospital deaths (one case of staged surgery and one of simultaneous it) 2012 M. Amano et al [ 7 ] One case after TAR Three staged surgery (first: esophagectomy and esophagostomy, second: re-replacement, Third: esophageal reconstruction) Discharge 2013 H. Munakata et al [ 8 ] One case after TEVAR Two staged surgery (First: aortic replacement, esophagectomy and esophagostomy, Second: retrosternal gastric bypass) Discharge 2019 A. Kamigaichi et al [ 9 ] One case after TEVAR Three staged surgery (first: esophagectomy and esophagostomy, second: aortic replacement, Third: esophageal reconstruction) Discharge …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation